Enforcement of mortagage by commercial banks in circumstances influenced by undue influence: Analysis of the law and practice - Mtui, Yustawinnie Vitalis (Mzumbe University, 2024)
A dissertation submitted in partial fulfilment for the requirement of the award of degree of masters of laws (LLM-Commercial Law) of Mzumbe University